The impact of NT-proBNP on admission for early risk stratification of patients undergoing primary percutaneous coronary intervention - Ayhan, Erkan; Isik, Turgay; Uyarel, Huseyin; Ergelen, Mehmet; Cicek, Gokhan; Ozyurtlu, Ferhat; Ghannadian, Bahman; Tanboga, Ibrahim Halil (My University, 2013)
Background: Incompleted ST segment resolution (STR) after primary percutaneous coronary intervention (PCI) is associated with worse clinical outcomes.